On the interplay of segmentation cues in adult OV/VO bilinguals: prosody, frequency and context language - Irene de la Cruz-Pavía; Gorka Elordieta; Itziar Laka (Anuario del Seminario de Filología Vasca "Julio de Urquijo")
The present study investigated the role of phrasal prosody in speech segmentation in adult bilingual speakers of two languages with opposite basic word orders: Basque and Spanish (Object-Verb and Verb-Object, respectively). We created a structurally ambiguous artificial language (AL) that allowed two possible parses, mimicking the order characteristic of OV and VO languages, and enriched it with the prosodic cue associated to languages with an OV order: a pitch contrast, in which the element receiving prominence within phrases has higher pitch than the non-prominent elements. We tested highly proficient L1Basque-L2Spanish and L1Spanish-L2Basque speakers on their segmentation preferences of the AL, addressing both groups in their respective L1 during the study. Analysis of their segmentation preferences revealed that the presence of OV prosody modulated—but did not determine—their parsing of the ambiguous AL, as both groups of bilinguals exhibited a significantly greater preference for the segmentation associated to OV languages than two similar groups presented with a prosodically flat variant of the same AL in de la Cruz-Pavía et al. (2022). These results confirm that phrasal prosody is an available segmentation cue for adult bilinguals, but suggests it is not a salient segmentation cue in this population.